2020
DOI: 10.1002/macp.202000257
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Cytotoxicity Evaluation of Zinc Oxide–Bacterial Cellulose–Chitosan Hydrogels for Antibacterial Dressing

Abstract: Lin et al. evaluated the cell compatibility and antibacterial activity of bacterial cellulose-chitosan (BC-CS) membranes in vitro. [6] BC is widely used in antibacterial aspects. Wu et al. proposed a preparation method of slow-released antimicrobial wound dressing. [7] Common antibacterial agents for improving BC include benzalkonium chloride, [8] copper, silver, ZnO nanoparticles, sulfadiazine silver, [9] polyhexamethylene guanidine hydrochloride (PHMB), [10] sericin, CS, propolis, [11] and so on. Recently, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 41 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Therefore, two antimicrobial factors were chosen to fabricate the paper coating to obtain the additive effect. Other published papers employ the same strategy, i.e., the use of two antimicrobial agents [ 23 , 36 ]. The assay of antimicrobial activity of the composites revealed that the combination of chitosan and ZnO was more effective than chitosan alone and led to a 100% reduction in bacterial titer, while paper coated with pristine chitosan exhibited a 96.36% reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, two antimicrobial factors were chosen to fabricate the paper coating to obtain the additive effect. Other published papers employ the same strategy, i.e., the use of two antimicrobial agents [ 23 , 36 ]. The assay of antimicrobial activity of the composites revealed that the combination of chitosan and ZnO was more effective than chitosan alone and led to a 100% reduction in bacterial titer, while paper coated with pristine chitosan exhibited a 96.36% reduction.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one research article covered the use of chitosan, bacterial cellulose, and ZnO [ 23 ]. However, the application and processing of the components differed from the method applied in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are many other approaches which use combinations of different formulations together with chitosan to improve its antimicrobial effects. Specifically, for wound dressings, many different formulations and approaches have been applied to improve their antibacterial activity, such as: silver formulations [ 138 , 139 ], zinc oxide [ 140 ], nitric oxide [ 104 ], ferulic acid [ 141 ], etc. Through carboxymethylation and selective oxidation of bacterial cellulose and cross-linking with chitosan, Xie et al produced a cellulose–chitosan wound dressing that inhibited bacterial proliferation and exhibited an 80% wound-healing rate after three weeks.…”
Section: Cellulose–chitosan Functional Biocompositesmentioning
confidence: 99%
“…Most of the studies in the literature were performed using silver nanoparticles, however, also some different nanoparticles can be found, namely copper (Ponco and Helmiyati, 2020), gold (Mahmoud et al, 2019), zinc oxide (Kai and Xuesong, 2020) silver-titanium dioxide nanoparticles as an antibacterial agent. The kinetics of drug release was performed by using various mathematical models, where the Higuchi model was found to be the best fit.…”
Section: Additional Nanoparticlesmentioning
confidence: 99%